Microscopic changes over time in human dermis after exposure to sodium hydroxide. Issue 2 (April 2022) - Fujioka, Masaki; Fukui, Kiyoko; Yoshino, Kentaro; Noguchi, Miho; Soeda, Momoko; Ito, Masahiro
Highlights: Alkali injuries skin rapidly and progressively, until it is neutralized or removed. It has not been decided when to operate for alkaline skin injury. Alkaline degeneration extended to the middle dermis in about 24 h. Tangential excision within 24 h might prevent further damage. Abstract: Alkaline substances injurie skin rapidly and progressively, until they are neutralized or removed. They usually continue to invade the tissue, resulting in deep ulcers. In order to examine the dermal change after exposure to alkaline substance, the debrided skin of a patient with sodium hydroxide injury was observed to change over time under a microscope. A patient who had a chemical injury of his forearm after exposure to sodium hydroxide solution underwent full-thickness skin debridement 6 h after the injury. We observed the degeneration of the dermis of this resected specimen over time Histological findings indicated that the narrow border zone of neutrophils separated the zone containing degenerated collagen fibers from normal tissue, and alkaline denaturation of the dermis was found to spread to the middle layer of the dermis in about 24–48 h. Our results suggested that early tangential excision within 48 h could completely remove alkaline substances and prevent further deep soft tissue damage.